1992
DOI: 10.1007/bf00873128
|View full text |Cite
|
Sign up to set email alerts
|

Phase II clinical and pharmacological study of didemnin B in patients with metastatic breast cancer

Abstract: Sixteen evaluable patients with metastatic breast cancer were entered into a phase II trial of didemnin B. They received the drug at an initial dose of 5.6 mg/m2 every 21 to 28 days. Major toxicities noted were myalgia and nausea and vomiting while myelosuppression was mild. There were no complete responses; however, two minor responses were observed. The pharmacokinetics of didemnin B were studied in 10 patients who received the drug as 30 to 60 min i.v. infusions. A sensitive competitive inhibition enzyme im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…The notion of improved therapeutic ef®cacy in a continuous exposure regime is also consistent with the report by Benvenuto et al 21 showing that didemnin B undergoes rapid clearance in vivo. Given the authors' determination of a circulating half-life for didemnin B of less than 5 hr, it is possible to speculate that the poor ef®cacy shown in Phase II trials might be due to the dose schedules used.…”
Section: C L I N I C a L T R I A L Ssupporting
confidence: 76%
See 3 more Smart Citations
“…The notion of improved therapeutic ef®cacy in a continuous exposure regime is also consistent with the report by Benvenuto et al 21 showing that didemnin B undergoes rapid clearance in vivo. Given the authors' determination of a circulating half-life for didemnin B of less than 5 hr, it is possible to speculate that the poor ef®cacy shown in Phase II trials might be due to the dose schedules used.…”
Section: C L I N I C a L T R I A L Ssupporting
confidence: 76%
“…Because of the poor clinical performance and limited biological half-life of didemnins in vivo, 21 there has been some focus on the replacement of the macrocyclic ester bonds of didemnins. The ®rst example of such an analog was reported by Katauskas and Rinehart 108 in which the ester bond between Hip 2 and Ist 1 ( Fig.…”
Section: Modi®cations To the Macrocyclic Backbonementioning
confidence: 99%
See 2 more Smart Citations
“…A trial with cancer patients revealed biphasic clearance from plasma, with a t 1/2 a of 0.12 h, and a t 1/2 b of 4.8 h [32]. This study characterized elimination, tissue concentrations and metabolism of tritiated didemnin B over time using male mice dosed i.p..…”
Section: Introductionmentioning
confidence: 97%